Chinese funerary biographies : an anthology of remembered lives - Ebrey, Patricia Buckley, 1947-; Yao, Ping (Professor of history); Zhang, Cong, 1967- (Seattle : University of Washington Press, 2019)
"Tens of thousands of epitaphs or funerary biographies survive from imperial China. Written to be engraved on stone and placed in a grave, they typically focus on the deceased's biographical information and exemplary words and deeds, expressing survivors' longing for the dead. Epitaphs provide glimpses of the lives of people who are not well-documented in such sources as the dynastic histories and local gazetteers: women, men who did not leave a mark politically, and children. This anthology makes available a set of funerary biographies covering nearly two thousand years of history, from the Han dynasty through the nineteenth century, selected for their potential as teaching material for courses on Chinese history, literature, and women's studies as well as world history. Funerary biographies, due to their inclusion of telling details about personal conduct, family life, local conditions, and social, cultural, and religious practices, can illustrate ways of thinking and the realities of daily life. Since most funerary biographies can be read and analyzed on multiple levels, they have the potential to stimulate discussion of topics such as the emotional tenor of family life, rituals associated with death, whether the values seen in these biographies should be called Confucian, ways to analyze women's lives from sources written by men, and how to use sources that can be assumed to be biased. These biographies will be especially effective when combined with more readily available primary sources such as official documents, religious and intellectual discourses, and anecdotal stories, promising to generate interesting discussion about literary genre, the ways historians use sources, and how writers shape their accounts"--
Three short eastern Han funerary biographies : epitaphs for Ma Jiang (34-106), Wu Zhongshan (ca. 92-172), and Kong Dan (fl. 182) / translated by Ping Yao and Patricia Ebrey -- A Chinese general serving the northern Wei state : entombed epitaph for the late Wei dynasty overseer of military affairs, Sima Yue (462-508) / translated by Timothy Davis -- A twice-widowed Xianbei princess : epitaph with preface for the Great Enlightenment Temple nun surnamed Yuan (475-529) / translated by Jender Lee -- Authoring one's own epitaph : self-authored epitaph / by Wang Ji (590-644) ; Inscription dictated while near death / by Wang Xuanzong (633-686) ; translated by Alexei Kamran Ditter -- Wives commemorating their husbands : epitaph for Cao Yin (fl. 7th century) / by Madame Zhou (fl. 7th century) ; Epitaph for He Jian (686-742) / by Madame Xin (fl. 742) ; translated by Ping Yao -- A married daughter and a grandson : entombed funerary inscription for my daughter the late Madame Dugu (785-815) and entombed record for my grandson (803-815) who died young (Quan Shunsun, 803-815) / by Quan Deyu (759-818) ; translated by Anna Shields -- A nun who lived through the Huichang persecution of Buddhism : epitaph for Daoist nun (Zhi Zhijian, 812-861) / by Zhi Mo (fl. 860) ; translated by Ping Yao -- An envoy serving the Kitan Liao Son of Heaven : epitaph for Han Chun (d. 1035), court ceremonial commissioner / by Li Wan (fl. 1012-1036) ; translated by Lance Pursey -- Epitaphs made widely available : funerary biographies for three men of Luzhou: Liang Jian (d. 1042), Wang Cheng (d. 1042), and Chen Hou (1065-1123) / translated by Man Xu -- A friend and political ally : funerary inscription for Mr. Culai (Shi Jie, 1005-1045) / by Ouyang Xiu (1007-1072) ; translated by Cong Ellen Zhang -- Preserving a father's memory : funerary inscription for Chao Juncheng (1029-1075) / by Huang Tingjian (1045-1105) / translated by Cong Ellen Zhang.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on January 14, 2020).
eBooks on EBSCOhost
Keywords: Inscriptions -- China; Epitaphs -- China; China -- Biography; Funeral rites and ceremonies -- China; Burial -- China; China -- Social life and customs -- Sources; Épitaphes -- Chine; Funérailles -- Rites et cérémonies -- Chine; Sépulture -- Chine; Chine -- Mœurs et coutumes -- Sources; HISTORY -- Asia -- China; Burial; Epitaphs; Funeral rites and ceremonies; Inscriptions; Manners and customs; China; collective biographies; epitaphs; Biographies; Sources; Epitaphs; Biographies; Biographies; Épitaphes.